Predictive factors for spasticity among ischemic stroke patients - Moura, Rita de Cássia dos Reis [UNIFESP] (2009)
Spasticity is a determining for functional loss following ischemic stroke. OBJECTIVE: To detect possible predictive factors for its occurrence. METHOD: Demographic, clinical and tomographic data on 146 stroke patients were analyzed. RESULTS: Spasticity was noted more frequently among patients who underwent physiotherapy (p<0.0001; OR=19.4; 95% CI: 4.4-84.5), those who underwent such treatment for long periods (p=0.028; OR=4.80; 95% CI: 1.1-8.3) and those with manual work (p=0.041; OR=2.2; 95% CI: 1.02-4.6), lower income (p=0.038), pain complaints (p<0.0001; OR=107.0; 95% CI: 13.5-847.3), appearance of pain at the same time as spasticity (p<0.0001), previous vascular disease (p=0.001; OR=4.2; 95% CI: 1.7-10.3), muscle weakness (p<0.0001; OR=91.9; 95% CI: 12.0-699.4), extensive lesions as seen on tomography (p=0.01) and lesions affecting more than one cerebral lobe (p=0.018). Manual work had a relative risk of 2.9; previous stroke 3.9, and extensive lesion 3.6. CONCLUSION: Spasticity affected 25% of the patients, and was associated with: manual work, previous stroke, extensive lesions, decrease in individual income, underwent physiotherapy, underwent physiotherapy for longer period, pain complaints, the pain started simultaneously with the spasticity, presented changes in strength.